2020
DOI: 10.17211/tcd.811297
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of the students of the geography departments towards online learning

Abstract: geography departments that practice face-to-face education in universities have had to switch to online education in line with the technological infrastructure of universities. The online learning practices of geography science, which examine human and physical elements with both theoretical and applied studies, also have to differ. In this study, the attitudes of geography students who were forced to receive online education instead of studying face-to-face due to the mandatory conditions imposed by Covid-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…However, other studies reported that attitudes towards e-learning did not change based on gender. 20,29,[37][38][39][40][41][42] The high attitude scores of female students in the present study towards e-learning can be explained by women having a greater sense of responsibility.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies reported that attitudes towards e-learning did not change based on gender. 20,29,[37][38][39][40][41][42] The high attitude scores of female students in the present study towards e-learning can be explained by women having a greater sense of responsibility.…”
Section: Discussionmentioning
confidence: 97%
“…Ölçekten alınabilecek puan 20 ile 100 arasında değişmektedir. Elde edilen puanın yüksekliği oranında öğrenciler olumlu tutuma sahiptir (18,23,24). Ölçek Cronbach alpha güvenirlik katsayısı genel kabul alt boyutu için 0,77, bireysel farkındalık alt boyutu için 0,85, kullanışlılık alt boyutu için 0,79 uygulama etkililiği alt boyutu için 0,68 ve tüm ölçek için 0,904 olarak bulunmuştur (18).…”
Section: Gereç Ve Yöntemler Araştırmanın Türüunclassified
“…Coğrafya öğretiminin yapısal özelliklerini ve becerilerin türlerini uzaktan eğitimle öğrencilere kazandırılması örgün eğitim kadar kolay olamayacağı için uzaktan coğrafya eğitimleri farklı anlayış içerisinde verilmelidir (Sarıbaş ve Meydan, 2020). Coğrafya öğretmenlerinin uzaktan eğitim ile ilgili görüşlerini yansıtan benzer çalışmaların ülkemizde ve farklı ülkelerde yapılması gelecekte bu tür salgınlar karşı mücadele ve salgın döneminde eğitim konusunda alınacak önlemeler bakımından önemlidir.…”
Section: Sonuç Ve öNeri̇lerunclassified